Six steps to successful child advocacy changing the world for children - Wright, Amy Conley; Jaffe, Kenneth J. (SAGE, 2014)
This text offers an interdisciplinary approach to child advocacy, nurturing key skills through a proven six-step process that has been used to train child advocates and create social change around the world. The approach is applicable for micro-advocacy for one child, mezzo-advocacy for a community or group of children, and macro-advocacy at a regional, national, or international level. The text offers skill-building activities and includes timely topics such as how to use social media for advocacy
Keywords: Kind; Children's rights; Child welfare; Children -- Social conditions; Children -- Services for